The Process of Converting Conventional Nagari Banks to Sharia Nagari Banks in Indonesia - Saleh, Rahmat; Zetra, Aidinil; Putera, Roni Ekha (Universitas Teuku Umar, 2024)
Policy transfer to a banking company owned by the Regional Government has wide complexity. The status of Banks Regional Banks as Regional Owned Enterprises must refer to Government Regulation No. 54 of 2017 and Minister of Home Affairs Regulation Number 32 of 2018 as a form of obedience in government governance. As a banking company, Regional Banks must comply with Law No. 10 of 1998 concerning banking as a form of corporate governance. The purpose of this study is to explore the policy transfer process in converting Bank Nagari from a conventional bank to an Islamic bank in West Sumatra, with a focus on comparing it to other regional banks in Indonesia that have successfully transitioned. This research aims to analyze the motivations of the policy actors involved, identify the key actors in this policy transfer, and examine the factors that support or hinder the process. This research uses a descriptive qualitative method, a case study approach using Dolowitz & Marsh's theory in analyzing the motivations of the actors involved in the policy transfer process studied, the core actors in policy transfers, and the inhibiting factors in the policy transfer process studied. Unsmooth policy transfers occurred in this case, dominated by the influence of political parties, and only after analyzing secondary data that appeared in the public sphere. Further research is needed to examine more deeply the political dynamics that occur in the process of converting Conventional Nagari banks into Sharia Nagari Banks.